VISUAL BASIC 6.0 INFORMATION PRESENTATION SUPPORT COSTS AS A LAUNDRY IN CV. BATAVIA GARMENT INDUSTRY - Teddy Ismanto; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2001)
CV. Batavia Garment Industry is a business entity engaged in the laundry services,particularly for entrepreneurs and businessmen convection rental apparel. But inhandling the problem still use the evidence in the form of bill / receipt. Viewing thesecircumstances, the authors propose kepihak services company to provide computerbasedinformation using Visual Basic 6.0 software assistance.The author here gives recommendations to companies about issues ayaran Pemblaundry costs. Among these officers can enter data directly into a customer, the typeof goods entering without having to record through the evidence for the bill.